Comparing Fiscal Indicators - Colwell, Peter F.; Lash, Nicholas A. (The Review of Economics and Statistics, 1973)
HIS paper reviews the evolution of fiscal T indicators from changes in the Federal budget to the initial impact variables. The highly touted full employment surplus has severe weaknesses as a measure of exogenous actions.' Attempts to correct these weaknesses have led to the development of various alternative indicators. Of these, the indicators measuring the initial impact of fiscal policy changes appear to be the most promising.2